PERAN REMITAN TENAGA KERJA INDONESIA TERHADAP POTENSI PENGURANGAN RISIKO BENCANA BANJIR DI WILAYAH PERKOTAAN INDRAMAYU - Saut Sagala; Alpian A Pratama; Teti A Argo; A Asirin (TATALOKA, 2012)
This research explores the phenomenon of community adaptation in a disaster prone area by working as an Indonesian Foreign Labor and the contribution of their remittances to reduce disaster risk. The case study of this research is located in urban area of Indramayu which is potentially affected by flood disaster due to sea level rise. 237 respondents consisting of ex TKI worker and their family were interviewed with a structured questionnaire related with the characteristics of TKI, the amount of remittance and it’s pattern, as well as its potential for flood risk reduction. Based on statistical analysis, it is found that the remittance use can be categorized into four classifications, i.e. consumption, physical, saving, and capital investment. Further analysis shows that the capital investment and saving can function as a long-term adaptation while physical allocation can contribute for flood risk mitigation at household level. The remittance potential could be enhanced if it is used collectively